The Complex Italianità of Gianni Angelo Grohovaz - Eisenbichler, Konrad (Italian Canadiana, 2022)
Being Italian is not as simple or as straightforward as one might assume. For an Italian from the territories that Italy ceded to Yugoslavia in the wake of the Second World War, identifying as Italian, or to be seen as an Italian, was problematic, if not even dangerous. During and after the Second World War, most Italians from these territories abandoned their hometowns and became refugees in Italy. Some then emigrated overseas, where, for the most part, they continued to self-identify as Italians. This article looks at the Italian-Canadian author, radio personality, and activist Gianni Angelo Grohovaz, originally from Fiume (Italy), to determine what being Italian meant for him and how it conditioned his life and work.